Dopaminergic activity and altered reward modulation in anorexia nervosa—insight from multimodal imaging. Issue 5 (18th October 2016) - Bailer, Ursula F.; Price, Julie C.; Meltzer, Carolyn C.; Wagner, Angela; Mathis, Chester A; Gamst, Anthony; Kaye, Walter H.
ABSTRACT: Objective: Individuals with anorexia nervosa (AN) have anxious and inhibited temperaments with high concern for consequences. Studies using either positron emission tomography (PET) or functional magnetic resonance imaging (fMRI) suggest involvement of the middle and dorsal caudate (DC) in individuals recovered (REC) from AN. For example, dopamine (DA) D2/D3 receptor binding in the middle caudate and DC was associated with anxiety and harm avoidance, and blood‐oxygen‐level‐dependent (BOLD) response in the DC was positively related to trait anxiety. It has not been shown yet whether BOLD response in individuals REC from AN was related to DA function. Methods: Post‐hoc correlation analyses between the PET and fMRI studies by correlating D2/D3 binding in striatal regions and BOLD signal in the anteroventral striatum (AVS) and DC for wins and losses respectively in 12 individuals REC from AN. Results: Individuals REC from AN with the greatest BOLD response in the DC in a monetary choice task had higher middle caudate D2/D3 binding, and greater anxiety and/or harm avoidance. Discussion: Though preliminary, these findings suggest that increased dorsal striatal D2/D3 binding is associated with enhanced cognitive response to feedback, potentially related to anxious anticipation of consequences. © 2016 Wiley Periodicals, Inc.(Int J Eat Disord 2017; 50:593–596)